2015
DOI: 10.1007/s12011-015-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Super High Dosing with a Novel Buttiauxella Phytase Continuously Improves Growth Performance, Nutrient Digestibility, and Mineral Status of Weaned Pigs

Abstract: This study was conducted to evaluate the efficacy of a novel Buttiauxella phytase to pigs fed P-deficient, corn-soybean meal diets. One hundred and twenty crossbred piglets (9.53 ± 0.84 kg) were allocated to one of five treatments which consisted of four low P diets (0.61 % Ca and 0.46 % total P) supplemented with 0, 500, 1,000, or 20,000 FTU/kg phytase as well as a positive control diet (0.77 % Ca and 0.62 % total P). Each treatment had six replicated pens with four pigs per pen. Pigs were fed the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
6
21
1
Order By: Relevance
“…As expected, pigs fed the NC diet with reduced P, Ca and ME had lower ADFI, ADG and G:F compared with those receiving the PC, which is in agreement with many previous studies ( Kies et al., 2006 , Zeng et al., 2015 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, pigs fed the NC diet with reduced P, Ca and ME had lower ADFI, ADG and G:F compared with those receiving the PC, which is in agreement with many previous studies ( Kies et al., 2006 , Zeng et al., 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, new phytase enzymes have been produced, including a Buttiauxella sp. phytase that are more efficacious in improving total tract P digestion and conferred additional benefits at dose rates above 500 FTU/kg ( Bento et al., 2012 , Zeng et al., 2015 ). Trials with broiler chickens noted a higher efficacy of Buttiauxella phytase when compared with Escherichia coli phytases ( Kumar et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, here we show that the negative outcome of protein-deficient diets on daily weight gain, final body weight and protein efficiency ratio of pigs is alleviated when these diets are supplemented with a CEP with no adverse effects of reduced dietary Ca and P. Similar positive effects for microbial phytase [ 20 , 21 , 22 , 23 , 24 , 25 ] and a CEP [ 34 , 35 ] were reported in the nursery, growing and finisher pigs fed with adequate protein but Ca and P deficient diets. The beneficial effect of CEP on the growth performance of pigs in both Ca and P adequate and deficient diets might be due to improvement in the utilization of Ca, P, and other nutrients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 81%
“…The most common type of exogenous phytase used in the swine diet is microbial phytase. There is a plethora of evidence that digestibility and utilization of P and Ca are increased in pigs when microbial phytase was supplemented in their diets formulated with adequate Ca and P [ 16 , 17 , 18 , 19 ] or reduced Ca- and P [ 20 , 21 , 22 , 23 , 24 , 25 ]. However, there are conflicting reports on the effects of microbial phytase on the digestibility of N and amino acids in pigs [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 No data available for cells containing "-". ◊ ity over and above the expected improvements in P and Ca (Adedokun et al, 2015;Zeng et al, 2015), and this, combined with the differential pH optimum of Buttiauxella sp. phytase, which allows for nutrient release higher in the digestive tract (Menezes-Blackburn et al, 2015), will contribute to the reduction in weight loss demonstrated in this study.…”
Section: Discussionmentioning
confidence: 91%